2005
DOI: 10.1002/bdra.20191
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐β3 promotes mesenchymal cell proliferation and angiogenesis mediated by the enhancement of cyclin D1, Flk‐1, and CD31 gene expression during CL/Fr mouse lip fusion

Abstract: TGF-beta3 promoted cell proliferation and angiogenesis in lip mesenchymal tissues. These events led to enhanced lip fusion in the presence of TGF-beta3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 35 publications
3
22
0
Order By: Relevance
“…It has been demonstrated that BMSCs secrete angiogenic and anti-apoptotic factors that stimulate proliferation of endothelial cells and smooth muscle cells (26)(27)(28)(29). In the present study, RT-PCR results indicated that the expression levels of VEGF, vWF, TGF-3β and IL-1β in the infarction zone were significantly increased in the BMSC group compared with the control group.…”
Section: Discussionsupporting
confidence: 54%
“…It has been demonstrated that BMSCs secrete angiogenic and anti-apoptotic factors that stimulate proliferation of endothelial cells and smooth muscle cells (26)(27)(28)(29). In the present study, RT-PCR results indicated that the expression levels of VEGF, vWF, TGF-3β and IL-1β in the infarction zone were significantly increased in the BMSC group compared with the control group.…”
Section: Discussionsupporting
confidence: 54%
“…Our data suggest that the elevation of TGF-b3 could promote angiogenesis in developing lips, and mediated by increased Flk-1 and CD31 expression. In the presence of TGF-b3, we also detected upregulation of Cyclin D1 expression, suggesting that TGFb3 promoted cell proliferation [12].…”
Section: Promotion Of Scarless Repair and Angiogenesis In Cleft Lip Omentioning
confidence: 80%
“…We also detected mesenchymal cells immunopositive for Flk-1 and CD31, markers for endothelial cell precursors. In addition, embryonic lips isolated from 11.5-day-old CL/Fr mouse embryos were allowed to develop in serum-free organ cultures in the presence or absence of TGF-b3 [12]. Lips developed fused in 2 days normally and exogenous TGF-b3 accelerated lip fusion in these cultures.…”
Section: Promotion Of Scarless Repair and Angiogenesis In Cleft Lip Omentioning
confidence: 99%
“…Bijl et al [11] stated that anxiety levels of the midazolam group of patients were significantly less than the corresponding anxiety levels of the placebo group Kaufman et al [5] stated that all modes of sedation were found to be effective in reducing anxiety. In their study Burstein et al [19] evaluated midazolam following intranasal administration to adult dental surgery patients and to ascertain the effect of midazolam on anxiety. Anxiety was evaluated using a 100-mm visual analogue scale and they stated that there was a reduction in anxiety score.…”
Section: Journal Of Dental and Craniofacial Researchmentioning
confidence: 99%